IMPLEMENTASI BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN (BPJS KESEHATAN)TERHADAP PERSAINGAN USAHA RUMAH SAKIT DI KOTA PEKANBARU - Has, Randi Awara; Hasanah, Ulfia; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Social security is designed to assist individuals or groups in order to achieve the standard of living and health are more satisfying to the individual and social relationships allow them to develop their full capacity and promote their well-being in continuity, but if the implementation of its impact on competition business can define as competition between sellers and buyers in the market to seize.Because, basically, competition in the business world can be understood as a positive activity in daily life, every economic actor would enter the market through a competitive process in which producers tried to take a way to improve the quality and service in an effort to win the market and consumers.But when their monopolistic practices that lead to business actors become efficient and able to increase barriers to market entry for competitors, the potential conflict with the principle of fair competition can take place her special connection with suspicions of anti-competition fair. This type of research using sociological research, which meant an immediate interview persons that hospitals Lancang Kuning, Petala Bumi, Santa Maria, and Arifin Achmad.This study aims to identify and explain the impact of implementation of the competition BPJS hospital in Pekanbaru. The problems discussed in this thesis is, first, how the implementation BPJS in the review of competition law in the hospital in the city of Pekanbaru? Second, what solution or an attempt to avoid the occurrence of unfair competition at a hospital in the city of Pekanbaru?These results indicate the organization of health BPJS pose unfair competition to the hospital in the city of Pekanbaru. Competition Supervisory Commission Council attempt to analyze more deeply about the impact of the implementation of BPJS whether that act has naturally restrict competition. After this research, it can be concluded that. BPJS Health, in this case the implementation of an impact on a number of businesses who can not participate. The need for regulation of tariff differences hospitals and adjustment requirements to be hospitalized as a partner BPJS.Keywords: Business Competition – BPJS Kesehatan